Uncovering paradoxes of compassion at work: a dyadic study of compassionate leader behavior - Krause, Vinzenz; Rousset, Célia; Schäfer, Björn (Frontiers in Psychology, 2023)
In today's business world, organizations tend to overlook that employees face suffering caused by work and non-work-related events that can negatively impact business organizations in the long run. One way to address this challenge is through leadership acknowledging and alleviating employees' suffering to ensure a company's success. However, research on compassion and leadership in business settings is still relatively scarce. In this study, we aim to extend the organizational compassion literature by addressing our research question: "What are paradoxes induced by compassionate leader behavior in the workplace in the context of social hierarchy?". We conducted a qualitative exploratory study based on 12 semi-structured interviews with six dyads of leaders and their direct subordinates from small, medium, and large firms representing different industries. Our study supports the proposal that compassion is an ambiguous and multifaceted social relation rather than a unidirectional approach that follows the persistent opinion of a powerful leader and an underprivileged member. By doing so, the study reveals novel insights into the dynamics between leader and member and provides evidence for the strategic (mis-)use of compassion within the organizational arena. The research data further demonstrate how leaders in business organizations currently practice compassion and outlines particular challenges inherent to the compassion paradoxes which can either promote or inhibit leadership compassion. Thus, the findings of our study contribute to management literature in the field of Positive Organizational Scholarship (POS) by highlighting compassion as a critical element of dyadic leader-subordinate relationships that could be reinforced by systematically building more competence in leaders and members to navigate the tensions emerging from the identified compassion paradoxes. Additionally, we provide limitations and recommendations for further research, along with several theoretical and practical implications of the results, which are particularly relevant for practitioners such as managing directors, leaders, employees, human resource managers, academics, and business and HR consultants.